The gliding phase in swimming: the effect of water depth - Marinho, D.A. (2011)
Aiming to achieve higher performances, swimmers should maximize each component of swimming races. During starts and turns, the gliding phase represents a determinant part of these race components. Thus, the depth position allowing minimizing the hydrodynamic drag force represents an important concern in swimming research. The aim of this study was to analyse the effect of depth on drag during the underwater gliding, using computational fluid dynamics